Teacher aspiration towards change in teaching and learning in secondary schools - Konting, Mohd. Majid; Ismail, Habsah; Wan Ali, Wan Zah; Hassan, Roshafiza (Faculty of Educational Studies, Universiti Putra Malaysia, 2009)
Teacher aspiration towards change in teaching and learning is pertinent with the introduction of educational initiatives aimed at producing spiritually, physically, emotionally and intellectually balanced students. Teaching and learning aspiration enables teachers to adapt and change their current classroom practices. Differences in teacher aspiration are based on organizational and student needs. The aim of this paper is to report the findings of a project which explores teachers' aspiration towards change in their classroom teaching and learning practices based on their demographic background. An instrument consisting of 24 items is used to measure teachers' aspiration. Data was gathered from a clustered sample of 254 National, 107 Cluster and 43 Technical Secondary School teachers in Malaysia. Findings of the study show that the mean score of teachers' aspiration towards change in teaching and learning of Cluster Secondary School teachers (Mean= 3.448, SD= 0.92) is significantly higher (F = 11.865, p<O.Ol) compared to their counterparts in the National Secondary School (Mean= 3.024, SD=0.790) and Technical Secondary School (Mean= 2.864, SD= 0.89). Implications of the findings are also discussed.